Scurvy and its Anaemia - Stewart, Brian Bronte (Department of Medicine, 2020)
Coming into contact with a case with clinical features of severe scurvy but having haematological features almost indistinguishable from severe pernicious anaemia, and yet obtaining an immediate and rapid haematological response to treatment with ascorbic acid, prompted me to consult the literature on the subject. Each new article read appeared to contradict the former so that I came away perplexed and confused. This confusion was easy to appreciate as deficiency of one vitamin usually means a deficiency in many other essential requirements. Consequently I felt that the dramatic haematological response was purely the result of supplying the necessary factor, in a case of nutritional macrocytic anaemia. This necessary factor was present in the full hospital diet given.